Enterprise content and search management for building digital platforms - Shivakumar, Shailesh Kumar (Hoboken : Wiley, 2016)
"Provides modern enterprises with the tools to create a robust digital platform utilizing proven best practices, practical models, and time-tested techniques Contemporary business organizations can either embrace the digital revolution & mdash;or be left behind. Enterprise Content and Search Management for Building Digital Platforms provides modern enterprises with the necessary tools to create a robust digital platform utilizing proven best practices, practical models, and time-tested techniques to compete in the today & rsquo;s digital world. Features include comprehensive discussions on content strategy, content key performance indicators (KPIs), mobile-first strategy, content assessment models, various practical techniques and methodologies successfully used in real-world digital programs, relevant case studies, and more. Initial chapters cover core concepts of a content management system (CMS), including content strategy; CMS architecture, templates, and workflow; reference architectures, information architecture, taxonomy, and content metadata. Advanced CMS topics are then covered, with chapters on integration, content standards, digital asset management (DAM), document management, and content migration, evaluation, validation, maintenance, analytics, SEO, security, infrastructure, and performance. The basics of enterprise search technologies are explored next, and address enterprise search architecture, advanced search, operations, and governance. Final chapters then focus on enterprise program management and feature coverage of various concepts of digital program management and best practices & mdash;along with an illuminating end-to-end digital program case study. Offers a comprehensive guide to the understanding and learning of new methodologies, techniques, and models for the creation of an end-to-end digital system Addresses a wide variety of proven best practices and deployed techniques in content management and enterprise search space which can be readily used for digital programs Covers the latest digital trends such as mobile-first strategy, responsive design, adaptive content design, micro services architecture, semantic search and such and also utilizes sample reference architecture for implementing solutions Features numerous case studies to enhance comprehension, including a complete end-to-end digital program case study Provides readily usable content management checklists and templates for defining content strategy, CMS evaluation, search evaluation and DAM evaluation Comprehensive and cutting-edge, Enterprise Content and Search Management for Building Digital Platforms is an invaluable reference resource for creating an optimal enterprise digital eco-system to meet the challenges of today & rsquo;s hyper-connected world"--
"Contemporary business organizations can either embrace the digital revolution--or be left behind. Enterprise Content and Search Management for Building Digital Platforms provides modern enterprises with the necessary tools to create a robust digital platform utilizing proven best practices, practical models, and time-tested techniques to compete in the today's digital world. Features include comprehensive discussions on content strategy, content key performance indicators (KPIs), mobile-first strategy, content assessment models, various practical techniques and methodologies successfully used in real-world digital programs, relevant case studies, and more. Initial chapters cover core concepts of a content management system (CMS), including content strategy; CMS architecture, templates, and workflow; reference architectures, information architecture, taxonomy, and content metadata. Advanced CMS topics are then covered, with chapters on integration, content standards, digital asset management (DAM), document management, and content migration, evaluation, validation, maintenance, analytics, SEO, security, infrastructure, and performance. The basics of enterprise search technologies are explored next, and address enterprise search architecture, advanced search, operations, and governance. Final chapters then focus on enterprise program management and feature coverage of various concepts of digital program management and best practices--along with an illuminating end-to-end digital program case study"--
14 Advanced Enterprise Search 398 -- 14.1 Federated Search 398 -- 14.2 Advanced Search Features 403 -- 14.3 Enterprise Semantic Search 409 -- 14.4 People Search and Social Search 412 -- 14.5 Mobile Search 415 -- 14.6 Big Data Search 415 -- 14.7 Search Engine Optimization (SEO) 417 -- 14.8 Case Study: Information Management Portal Driven by Apache Solr 422 -- 14.9 Chapter Summary 424 -- Further Reading 427 -- Index 429.
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Management -- Technological innovations; Digital media -- Management; Multimedia systems -- Management; Performance technology; Gestion -- Innovations; x; x; COMPUTERS -- Web -- Site Design; Management -- Technological innovations; Performance technology